A tanoncképzés rövidtávú munkaerőpiaci hatásai - Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2014)
– Although apprenticeship training has been praised for its effectiveness in smoothing the school-to-work transition of non-college bound students in Western European dual education systems, there is a lack of evidence from Central Eastern Europe. Using a unique individual-level panel database, which includes an extensive set of controls, the study shows that Hungarian vocational apprenticeship students from the non-college bound vocational training track and from the vocational secondary track have about 10-15% higher probability of initial employment, compared to similar graduates from the same track, who were trained in school. This effect seems to be stable across industries and robust to specification checks. It is also apparent that this effect is due to the apprenticeship students trained in medium or large size firms.
Keywords: I21; I24; J24; 330; apprenticeship training; unemployment; panel data